Effects of Ion-Transporting Proteins on the Digestive System Under Hypoxia - Xiang, Yiwei; Fan, Dongdong; An, Qimin; Zhang, Ting; Wu, Xianli; Ding, Jianhong; Xu, Xiaolin; Yue, Gengyu; Tang, Siqi; Du, Qian; Xu, Jingyu; Xie, Rui (Frontiers in Physiology, 2022)
Hypoxia refers to a state of oxygen limitation, which mainly mediates pathological processes in the human body and participates in the regulation of normal physiological processes. In the hypoxic environment, the main regulator of human body homeostasis is the hypoxia-inducible factor family (HIF). HIF can regulate the expression of many hypoxia-induced genes and then participate in various physiological and pathological processes of the human body. Ion-transporting proteins are extremely important types of proteins. Ion-transporting proteins are distributed on cell membranes or organelles and strictly control the inflow or outflow of ions in cells or organelles. Changes in ions in cells are often closely related to extensive physiological and pathological processes in the human body. Numerous studies have confirmed that hypoxia and its regulatory factors can regulate the transcription and expression of ion-transporting protein-related genes. Under hypoxic stress, the regulation and interaction of ion-transporting proteins by hypoxia often leads to diseases of various human systems and even tumors. Using ion-transporting proteins and hypoxia as targets to explore the mechanism of digestive system diseases and targeted therapy is expected to become a new breakthrough point.